Mechanisms of the Antinociceptive Action of Gabapentin - Jen-Kun Cheng; Lih-Chu Chiou (Elsevier, 2006)
Abstract.: Gabapentin, a γ-aminobutyric acid (GABA) analogue anticonvulsant, is also an effective analgesic agent in neuropathic and inflammatory, but not acute, pain systemically and intrathecally. Other clinical indications such as anxiety, bipolar disorder, and hot flashes have also been proposed. Since gabapentin was developed, several hypotheses had been proposed for its action mechanisms. They include selectively activating the heterodimeric GABAB receptors consisting of GABAB1a and GABAB2 subunits, selectively enhancing the NMDA current at GABAergic interneurons, or blocking AMPA-receptor-mediated transmission in the spinal cord, binding to the L-α-amino acid transporter, activating ATP-sensitive K+ channels, activating hyperpolarization-activated cation channels, and modulating Ca2+ current by selectively binding to the specific binding site of [3H]gabapentin, the α2δ subunit of voltage-dependent Ca2+ channels. Different mechanisms might be involved in different therapeutic actions of gabapentin. In this review, we summarized the recent progress in the findings proposed for the antinociceptive action mechanisms of gabapentin and suggest that the α2δ subunit of spinal N-type Ca2+ channels is very likely the analgesic action target of gabapentin. Keywords:: gabapentin, GABAB receptor, NMDA receptor, KATP channel, α2δ subunit of Ca2+ channels